Arsenic in Drinking Water and Incidences of Leukemia and Lymphoma: Implication for Its Dual Effects in Carcinogenicity - Lin, Ming-Hsien; Li, Chung-Yi; Cheng, Ya-Yun; Guo, How-Ran (Frontiers in Public Health, 2022)
Arsenic in drinking water has been recognized as carcinogenic to humans and can cause solid cancers of lung, urinary bladder, and skin. Positive associations have also been reported between arsenic ingestion and cancers of kidney, liver and prostate. Nevertheless, arsenic trioxide has been used successfully in the treatment of acute promyelocytic leukemia. Therefore, arsenic might play different roles in the carcinogenesis of solid cancers and hematologic malignancies. The relationship between arsenic in drinking water and the incidences of hematologic malignancies has not been fully investigated. We established a cohort of Taiwanese population and assorted 319 townships of Taiwan into two exposure categories using 0.05 mg/L as the cutoff. Then, we linked these data to the Taiwan Cancer Registry and computed standardized incidence ratios (SIRs) of lymphoma and leukemia by sex, exposure category and time period. The trend of changes in the SIRs over time was assessed, from 1981–1990 to 1991–2000 and then to 2001–2010. We found that in both lymphoma and leukemia, the higher exposure category was associated with lower SIRs in both men and women. In terms of time trends, the SIRs in both lymphoma and leukemia showed increasing trends in both sexes, while exposure to arsenic in drinking water decreased over time. The arsenic level in drinking water was negatively associated with the incidences of lymphoma and leukemia in both men and women. This study supports the dual effects of arsenic on carcinogenesis, with a potential protective effect against hematologic malignancies.